2020
DOI: 10.1158/1538-7445.am2020-5183
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 5183: The preclinical characterization of TST001, a novel humanized anti-claudin18.2 mAb with enhanced binding affinity and anti-tumor activity

Abstract: Claudin-18 isoform 2 (CLDN18.2) is a member of the human claudin family of tetraspan membrane proteins that are crucial structural and functional components of tight junctions. Unlike other family members, CLDN18.2 expression is strictly limited to differentiated epithelial cells of gastric mucosa. Interestingly CLDN18.2 was ectopically expressed at a significant level in multiple tumor types including gastric, esophageal, pancreatic and lung cancers, which makes it as an attractive anti-cancer target. TST001 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Although zolbetuximab is the first monoclonal antibody to target CLDN 18.2, a major limitation of its efficacy is that it can only be used in patients with high Claudin18.2 expression and is very limited in patients with low CLDN 18.2 expression. Osemitamab (TST001) is a monoclonal antibody with a higher affinity for CLDN 18.2 ( 35 ). ASCO recently published a prospective phase II clinical study of Osemitamab to explore the safety and efficacy of TST001 in combination with capecitabine and oxaliplatin (CAPOX) as a first-line treatment for advanced G/GEJ cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Although zolbetuximab is the first monoclonal antibody to target CLDN 18.2, a major limitation of its efficacy is that it can only be used in patients with high Claudin18.2 expression and is very limited in patients with low CLDN 18.2 expression. Osemitamab (TST001) is a monoclonal antibody with a higher affinity for CLDN 18.2 ( 35 ). ASCO recently published a prospective phase II clinical study of Osemitamab to explore the safety and efficacy of TST001 in combination with capecitabine and oxaliplatin (CAPOX) as a first-line treatment for advanced G/GEJ cancer.…”
Section: Discussionmentioning
confidence: 99%
“…TST001 is a novel humanized anti-CLDN18.2 IgG1 mAb with enhanced Fc binding affinity to FcγRIIIa (CD16a) and ADCC activity. In preclinical studies, TST001 upregulated PD-L1 expression on low-to-medium CLDN18.2-positive tumor cells and demonstrated stronger ADCC, CDC, and antibody-dependent cellular phagocytosis (ADCP) activity than zolbetuximab [48].…”
Section: Osemitamab (Tst001)mentioning
confidence: 99%
“…PFS and DoR for this cohort are ongoing (NCT04495296) [49]. The preclinical data showed that the antitumor efficacy of TST001 combined with an anti-PD-1 antibody and chemotherapy was more superior than the anti-PD-1 antibody with chemotherapy or combination of TST001 with chemotherapy [48]. Thus, TST001 in combination with the anti-PD-1 antibody nivolumab is being investigated in a phase I/II trial as a first-line treatment for metastatic gastric and GEJ adenocarcinoma (NCT04495296) [50].…”
Section: Osemitamab (Tst001)mentioning
confidence: 99%
“…In GC cell lines and patient-derived xenograft tumor models, TST001 showed more potent antitumor activity than zolbetuximab. Furthermore, the combination of TST001 with chemotherapeutic agents resulted in synergistic antitumor effects in these tumor models [ 80 ]. Currently, TST001 is being evaluated in phase I trials (NCT04396821 and NCT04495296) in both the US and China to assess its safety, tolerability, and antitumor activity in patients with advanced solid tumors, including but not limited to GC and PC.…”
Section: Introductionmentioning
confidence: 99%